Evaluasi Pemanfaatan Koleksi E-book dan E-journal Terhadap Kinerja Studi Mahasiswa UAJY Selama Masa Pandemi Covid (2020-2021) - Catharina Esmi Triningsih; Agung Nugrohoadhi (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Since March 24, 2020 Atma Jaya University Yogyakarta has started implementing distance learning so that teaching and learning activities is carried out online. UAJY supports units have adjusted the policy by providing online services. This of course will make it difficult for libraries to serve their collections. Service that was originally carried out face-to-face must be done online, such as book lending services, which can no longer be done in person. In order to continue to be able to assist users in accessing the information provided, library services are emphasized on online services such as electronic books (e-books) and electronic journals (e-journals). The presence of a collection of e-books and e-journals is expected to be able to meet the needs of users in finding reference sources. This research will be prioritized to explore answers to the following questions: How do students perceive online services to support to study performance? To what extent is the level of use of online collections (e-books and e-journals) in supporting to study performance? The method of this research is descriptive quantitative. Quantitative research with descriptive format aims to explain, summarize various conditions, situations, or variables that arise in the community that are the object of research based on what happened.